Harga, Kepercayaan, Kemudahan Penggunaan Aplikasi Dan Promosi Terhadap Keputusan Pembelian Online Di Shopee (Studi Pada Mahasiswa STKIP Dan STIE Widyaswara Indonesia Solok Selatan) - Septia Yuvira Fitri; Febsri Susanti (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This study aims to examine the effect of price, trust, ease of use of applications and promotions on online purchasing decisions at Shopee for STKIP and STIE Widyaswara Indonesia Solok Selatan students. This type of research is quantitative. The population in this study were students of STKIP and STIE Widyaswara Indonesia Solok Selatan. Where the number of STKIP students and STIE Widyaswara Indonesia Solok Selatan is 1.519 students. The sampling technique used was accidentalsampling, while the number of samples was 94 students obtained using the slovin formula. The type of data used in this research is quantitative data. While the data sources are primary and secondary data sources. Data analysis techniques use validity test, reliability test, descriptive analysis, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression and t test using SPSS version 21.00. The hypothesis was tested using the t test at α = 0.05. The results of this study indicate that price, trust, ease of use of the application and positive and significant impact on online purchasing decisions at Shopee for STKIP and STIE Widyaswara Indonesia Solok Selatan students.